Mapping Global Research Trends in Medicinal Plants: A Scientometric Analysis of Highly Cited Publications - Chaman Sab, M; Mueen Ahmed, KK; Bagalkoti, Vitthal (Information Research Communications, 2024)
Objectives This study aims to explore global research trends in medicinal plants by performing a scientometric analysis of highly cited publications. Methodology By analysing articles indexed in databases such as Web of Science, this research identifies influential authors, journals, countries, institutions, and thematic focus areas. Results The analysis offers insights into publication growth, collaboration patterns, citation impact, and emerging hotspots in medicinal plant research. offers a comprehensive overview of scholarly publications spanning from 1991 to 2022. A total of 200 documents were published across 115 sources, including journals, books, and other scholarly outlets. Despite the modest document count, the average citations per document are exceptionally high at 742.8. The top-cited papers, led by Bakkali et al., (5305 citations) and Cowan (4833 citations), predominantly focus on essential oils, antimicrobial agents, antioxidants, flavonoids, and natural products. Dominating the list is the Journal of Ethnopharmacology, with 21 publications, accounting for 10.5% of the top 200 papers. The United States (USA) stands out as the leading contributor, producing 40 records (20% of the top 200 papers) and receiving the highest total citations (35,376) with an Average Citation per Paper (ACP) of 884.4 and an h-index of 4, highlighting the widespread influence of its research output India. Conclusion Findings will help researchers, policymakers, and funding bodies understand this interdisciplinary domain's evolution and future direction.
Keywords: Medicinal plants; Scientometrics; Highly cited papers; Global research trends; Bibliometric analysis; Herbal medicine; Natural products